VALUE ENGINEERING PROYEK KONSTRUKSI BANGUNAN GEDUNG REKTORAT UNIVERSITAS YUDHARTA PASURUAN - Mochamad KHAMIM; Suselo Utoyo; Mohamad Zenurianto (Prokons: Jurnal Teknik Sipil, 2022)
AbstractApplication of Value Engineering is one technique that can be used to streamline costs. VE is applied to the Yudharta University Rectorate Building which has an area of 45 m long and 20 m wide, which is planned to have 13 floors of which the plan is to build 5 floors for offices and 6 floors for joint lectures, 1 floor for the hall and 1 basement for the parking area. With a total area ranging from 13,650 m2. In addition, due to the large volume of work, high job specifications, and the emergence of various types of materials for the same type of work. This study aims to determine the type of work with the highest cost, calculate life cycle costs, and calculate the percentage of savings from the total value of the budget plan.Keywords: Value Engineering, Alternative Design, value of the budget plan